2020
DOI: 10.1111/codi.15394
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide survey on proctological practice during COVID‐19 lockdown (ProctoLock 2020): a cross‐sectional analysis

Abstract: Aim Proctology is one of the surgical specialties that has suffered the most during COVID‐19 pandemic. Using a cross‐sectional non‐incentivised World Wide Web survey, we aimed to snapshot the current status of proctological practice in six world regions. Method Surgeons affiliated to renowned scientific societies with an interest in coloproctology were invited to join the survey. Members of the ProctoLock Working Group enhanced recruitment by direct invitation. The pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Elective surgery for benign conditions faced a cancelation of procedures to an estimate of 71.2-87.4% (2). The practice of surgical coloproctology was heavily affected by this lockdown, since most operations performed in this area were for benign, functional disorders (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elective surgery for benign conditions faced a cancelation of procedures to an estimate of 71.2-87.4% (2). The practice of surgical coloproctology was heavily affected by this lockdown, since most operations performed in this area were for benign, functional disorders (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Elective operations for coloproctological diseases suffered noticeably since they had been completely canceled at the time of the lockdown (4)(5)(6). Delayed surgery even for benign or functional disease may result in complications, unplanned emergency surgery, deterioration of individual health, disability, and social costs (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, 48,9% of the survey respondents reported a change in the initial surgical plan, and 26,3% reported a shift from elective to urgent operations. 5 Another worldwide survey on proctological practices conducted by Gallo et al 6 showed that 119 participants (11%) tested positive for SARS-CoV-2, and the participants from Asia reported a higher proportion of unaltered practice (17%). At the same time, those from Europe had the highest proportion of completely stopped practice (20%).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the authors 6 stated, "Surprisingly, PPE was deemed readily available by only 71% of respondents worldwide, ranging from <33% in Africa and South America to >80% in North America." This result may reflect resource management policies that do not always meet risk prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Lo que resulta muy interesante es cómo los profesionales en los hospitales han encontrado la manera de aprender rápidamente de la gran experiencia acumulada gracias a la metodología investigadora para terminar incorporando el conocimiento generado en su propia práctica y diseminándolo para que fuera útil a otros, durante la pandemia y como herramienta para la recuperación de la actividad programada (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionunclassified